2012
DOI: 10.1016/j.cyto.2012.06.236
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure and serum cytokine levels in healthy children

Abstract: Background Exposure to secondhand smoke (SHS) is associated morbidity in children. Alterations in immune responses may explain this relationship, but have not been well-studied in children. Our objective was to determine the association between SHS exposure and serum cytokine levels in healthy children. Methods We recruited 1–6 year old patients undergoing routine procedures. A parent interview assessed medical history and SHS exposure. Children with asthma were excluded. Blood was collected under anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
12
1
1
Order By: Relevance
“…Our study showed an insignificant association between maternal SHS exposure during pregnancy and maternal serum CRP levels. Regarding the associations between SHS exposure and three pro-inflammatory markers, IL-1β, IL-6 and TNF-α, Wilson et al found that healthy children exposed to SHS had lower serum concentrations of IL-1β than those without SHS exposure 23 , but an inverse association was observed in adults 24 and an insignificant association in adolescents was reported by Matsunaga et al 22 . Five studies found that SHS exposure had no significant effect on serum IL-6 in adolescents 22 23 and adults 9 21 24 , while a study in the elderly reported a significant association between SHS and elevated serum IL-6 levels 25 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study showed an insignificant association between maternal SHS exposure during pregnancy and maternal serum CRP levels. Regarding the associations between SHS exposure and three pro-inflammatory markers, IL-1β, IL-6 and TNF-α, Wilson et al found that healthy children exposed to SHS had lower serum concentrations of IL-1β than those without SHS exposure 23 , but an inverse association was observed in adults 24 and an insignificant association in adolescents was reported by Matsunaga et al 22 . Five studies found that SHS exposure had no significant effect on serum IL-6 in adolescents 22 23 and adults 9 21 24 , while a study in the elderly reported a significant association between SHS and elevated serum IL-6 levels 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the associations between SHS exposure and three pro-inflammatory markers, IL-1β, IL-6 and TNF-α, Wilson et al found that healthy children exposed to SHS had lower serum concentrations of IL-1β than those without SHS exposure 23 , but an inverse association was observed in adults 24 and an insignificant association in adolescents was reported by Matsunaga et al 22 . Five studies found that SHS exposure had no significant effect on serum IL-6 in adolescents 22 23 and adults 9 21 24 , while a study in the elderly reported a significant association between SHS and elevated serum IL-6 levels 25 . An insignificant association between SHS exposure and serum TNF-α was reported by four studies, two in adolescents 22 23 and two in adults 9 24 , and a positive association was reported by another study in adults 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Wilson et al [ 142 ] reported that exposure of children to secondhand smoke produced significant changes in cytokine levels particularly reducing the level of IFN- γ . As previously mentioned in the section on Pb, Lutz et al [ 137 ] reported an interaction of environmental risk factors in which Pb-exposed children also exposed to ETS had elevated IgE and IL-4 levels and altered T cell populations.…”
Section: Human Studies Involving Dit: Alphabetical List Of Risk Famentioning
confidence: 99%
“…14 Additionally, there is evidence that secondhand smoke exposure in children is related to differing levels of inflammatory cytokines. 15 In this study, we examined the association between cytokine levels in children with bronchiolitis and an asthma visit 6 months after discharge. We hypothesized that children with elevated Th2 cytokines (IL-4, IL-6 and IL-13) would be more likely to have a follow-up asthma visit compared with those with normal levels and that tobacco and marijuana smoke exposure would be associated with cytokine levels and asthma follow-up visits.…”
mentioning
confidence: 99%